Actividades lúdicas y su impacto en el aprendizaje cognitivo en los niños de Inicial II - Alvarado Rodríguez, Jenifer Solange (2025)
This research focused on analyzing the positive impact of games on cognitive learning in children, since games are not used to learn and thus rediscover knowledge. The methodology used was mixed with a descriptive approach and the method used was synthetic analytical, which allowed the problem of study to be broken down into its constituent parts and then integrated into a holistic analysis. The data set consisted of a sample of 30 children aged 4 to 5 years and a teacher. Structured observation in the classroom was used to analyze the behavior and attention level of children in class, as well as interviews with teachers to understand their perceptions of teaching strategies. The results obtained from this study show that the use of recreational activities within a formative process increases knowledge retention, motivation and active participation of school students. There is no doubt that educational games promote the development of fundamental cognitive skills such as memory, problem solving, logical thinking, as well as the development of creativity and teamwork, contributing to comprehensive and long-lasting learning. The systematic implementation of playful activities constitutes an effective pedagogical strategy to enhance cognitive learning in early education, because children learn better if they do it by playing, since they learn by doing it themselves.